Ekosistem Buatan Manusia Di Waduk Wonorejo - Afifa Sekar Safa'ah; Ira Iqlimatul A'yun; Istifadatul Mufidah; Moh Naufal Fajarul Mahfudzi; Sita Putri Nurul Azizah; Hany Nurpratiwi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
The Wonorejo Reservoir is a multi-purpose reservoir located in Wonorejo Village, Pagerwojo Sub-District, Tulungagung Regency, East Java Province, Indonesia. The Wonorejo Reservoir is a reservoir that is used to store water during the rainy season and is used during the dry season. Apart from being a water reservoir for the Wonorejo Reservoir also used for hydroelectric power (PLTA) and also for irrigation. Apart from that, this research also discusses the history of the establishment of the Wonorejo Reservoir, the purpose of establishing the Wonorejo Reservoir, the Benefits of the Wonorejo Reservoir, and the ecosystem in the Wonorejo Reservoir. This research was conducted with the aim of providing an explanation of what ecosystems exist in the Wonorejo Reservoir as well as its purposes, benefits and history. The research method used is descriptive qualitative by providing an explanation of the state of the ecosystem in the Wonorejo Reservoir. The data collection used an interview technique to one one office worker in the Wonorejo Reservoir.